Solar suitability map for office buildings using integration of remote sensing and Geographical Information System (GIS) - Omar R.C.; Wahab W.A.; Putri R.F.; Roslan R.; Baharuddin I.N.Z. (Institute of Physics Publishing, 2023)
Carbon dioxide; Coal combustion; Deforestation; Energy efficiency; Environmental management; Fossil fuels; Gas emissions; Global warming; Greenhouse gases; Natural resources; Office buildings; Remote sensing; Solar energy; Solar power generation; Solar power satellites; Urban growth; Anthropogenic greenhouse gas emissions; Carbon dioxide emissions; Cement manufacturing; Concentrated solar power; Metropolitan regions; Renewable energy source; Urban and rural areas; Use of renewable energies; Geographic information systems